Analisis Pengaruh Atribut Influencer Marketing Produk Elektronik pada Platform Youtube terhadap Customer Purchase Intention - Timothy Rey Laheba; The Jin Ai (University of Merdeka Malang, 2020)
The seemingly unlimited world makes competition increasingly fierce in the electronics industry. This phenomena makes the industry always look for ways to maximize the competitive advantage of the company. One of them is in marketing strategy. The use of influencer marketing is on the rise and will be able to increase the potential success of a product and brand on the market. But that does not mean the selection and use of influencer marketing can be done easily. Increasing of alternatives and expensive prices are the main problems during the selection process of influencer marketing that faced by industry. This study tries to find what attributes are the main focus for potential consumers in making product purchase decisions when watching video reviews on the Youtube platform. Data from 172 respondents were collected and analyzed in this research. It was found that the detail of product exposition is the most important attribute in making a purchase decision for a product and if execute well will ultimately increase customer purchase intentions of potential consumers who are using video reviews on the YouTube platform.